2000
DOI: 10.1006/dbio.1999.9475
|View full text |Cite
|
Sign up to set email alerts
|

Bilaterian Origins: Significance of New Experimental Observations

Abstract: Several recent laboratory observations that bear on the origin of the Bilateria are reviewed and interpreted in light of our set-aside cell theory for bilaterian origins. We first discuss new data concerning the phylogeny of bilaterian phyla. Next, we use systematic, molecular, and paleontological lines of evidence to argue that the latest common ancestor of echinoderms plus hemichordates used a maximal indirect mode of development. Furthermore, the latest common ancestor of molluscs and annelids was also indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 116 publications
(128 reference statements)
4
97
0
1
Order By: Relevance
“…These polarities reestablish the traditional view that heteronomous polychaetes are derived in relation to those with a largely homonomous pattern of segmentation (FAUVEL 1923). With Owenia positioned as the sister group of Enterocoela, several genetic patterns of tagmosis found in basal groups of deuterostomes (PETERSON et al 2000a) are also seen to be found in polychaetes, providing further empirical support for the present hypothesis.…”
Section: Mollusk-like Cleavagesupporting
confidence: 68%
“…These polarities reestablish the traditional view that heteronomous polychaetes are derived in relation to those with a largely homonomous pattern of segmentation (FAUVEL 1923). With Owenia positioned as the sister group of Enterocoela, several genetic patterns of tagmosis found in basal groups of deuterostomes (PETERSON et al 2000a) are also seen to be found in polychaetes, providing further empirical support for the present hypothesis.…”
Section: Mollusk-like Cleavagesupporting
confidence: 68%
“…Most directly developing marine bilaterians use much larger eggs that are able to produce embryos consisting of relatively large numbers of cells without feeding. Many lines of evidence show that for deuterostomes and lophotrochozoans maximal indirect development is primitive, and direct development is derived (36)(37)(38). A palentological argument against this view has been cited (39) based on some large eggs of Cambrian origin (40).…”
Section: Discussionmentioning
confidence: 99%
“…1). The Triploblastica encompasses the vast majority of animal phyla and species, and a great deal of research has been conducted in an attempt to explain the remarkable evolutionary radiation of this group (e.g., Peterson et al, 2000). Many human developmental regulatory genes and disease-related genes have clear orthologs in Nematostella, indicating that they must have originated prior to the cnidarian-triploblast split (Putnam et al, 2007;.…”
Section: Early Evolution Of Animal Stress-response Pathwaysmentioning
confidence: 99%